Clostridioides difficile colonization and infection in a cohort of Australian adults with cystic fibrosis. (July 2021) - Tai, A.S.; Putsathit, P.; Eng, L.; Imwattana, K.; Collins, D.A.; Mulrennan, S.; Riley, T.V.
Summary: Background: Little is known about Clostridioides difficile infection (CDI) in patients with cystic fibrosis (CF). The aim of this study was to investigate the prevalence, molecular epidemiology and risk factors for CDI in asymptomatic and symptomatic adults with CF in Western Australia. Methods: Faecal samples from symptomatic and asymptomatic patients were prospectively collected and tested for the presence of C. difficile by toxigenic culture. Ribotyping was performed by established protocols. Logistic regression analysis was performed to analyse the risk factors for C. difficile colonization and infection. Extensive environmental sampling was performed within the CF clinic in Perth. Results: The prevalence rates of asymptomatic toxigenic and non-toxigenic C. difficile colonization were 30% (14/46 patients) and 24% (11/46 patients), respectively. Fifteen ribotypes (RTs) of C. difficile were identified, of which non-toxigenic RT 039 was the most common. Among the symptomatic patients, the prevalence of toxigenic CDI was 33% (11/33 patients). Impaired glucose tolerance/diabetes mellitus and duration of intravenous antibiotic use in the past 12 months were significantly associated with increased risk of asymptomatic toxigenic C. difficile carriage and CDI. A trend towards higher CF transmembrane conductance regulator modulator treatment was observed in the CDI group. Extensive environmental sampling showed no evidence of toxigenic C. difficile contamination within the CF clinic. Conclusions: A high prevalence of asymptomatic carriage of toxigenic C. difficile was observed in adults with CF, comparable with that observed in the symptomatic CF population. There was no evidence of direct person-to-person transmission.